Readiness of Indonesian physics teachers to implement augmented reality-based learning - Haryanto, Zeni; Efwinda, Shelly; Sholeh, Muhammad; Anggraeni, Bening; Pasaribu, Dian Rachel (International Journal of Evaluation and Research in Education (IJERE), 2025)
In the 21st century, technological development has entered all aspects of life, including education. With its global potential, technology digitizes education, requiring teachers to use technology through media such as augmented reality (AR). This study aims to determine the readiness of physics teachers in Indonesia to implement AR-based learning. More specifically, this research explores the extent to which physics teachers are prepared based on aspects of alignment, capability, and engagement (ACE) in implementing AR-based learning. This exploratory research is conducted by distributing questionnaires with ACE aspects. This study involved several junior and senior high school physics teachers. Data analysis techniques use KH coder and quantitative descriptive. The results show that teachers already know the definition, features, and benefits of AR in learning (alignment aspect). Still, only a minority of teachers have implemented AR-based learning (capability aspect). In the engagement aspect, it is known that teachers want to learn more about how to create AR and implement AR effectively. The implications of this research are recommendations to stakeholders to encourage and facilitate teachers, especially physics teachers.